Working Memory and Intelligence Different Constructs Reply to Oberauer et al. (2005) and Kane et al. (2005). [article]. - Beier, Margaret E.
The authors address agreement and disagreements with the M. J. Kane, D. Z. Hambrick, and A. R. A. Conway (2005) and K. Oberauer, R. Schulze, O. Wilhelm, and H. M. SUB (2005) commentaries on P. L. Ackerman, M. E. Beier, and M. O. Boyle (2005). They discuss the following issues (a) the relationship between working memory (WM) and general intelligence (g), (b) the reanalyses included in the comments, (c) the use of a fixed effects model versus a random effects model for the meta-analysis, (d) the use of structural equation modeling analyses and structural coefficients as equivocal evidence for the relationship between WM and intelligence, and (e) the problem of confirmation bias in research on WM. Although the authors disagree with their commentators about the magnitude of relationship between WM and g. in the final analysis it appears that all concerned parties agree that WM and intelligence are different constructs. -- (from the author)